The effect of antibiotic and Morinda citrifolia waste bioactive as feed additive in layer ration - I.A. K Bintang; A. P Sinurat; Timothy Purwadaria (Jurnal Ilmu Ternak dan Veteriner, 2008)
A study on the use of zinc bacitracin antibiotic (ZnB) and Morinda citrifolia waste as feed additive in layer ration was conducted. One hundred and twenty pullet of Isa Brown strain were allocated into 5 treatments with 6 replications with 4 birds/replication. The treatment were: control, control + antibiotic (50 ppm Zinc bacitracin) and control + M. citrifolia waste at 3 levels (5, 10 and 15 g/kg ration). Analysis of variance was conducted in a completely randomized design. Variables measured were: feed intake, hen day (% HD), egg weight and feed conversion ratio (FCR). The results showed that feed intake of hens with M. citrifolia waste 5g/kg for 6 month was significantly (P<0.05) higher than that of control and M. citrifolia waste 10 g/kg. Between antibiotic and M. citrifolia waste was not significantly different (P>0.05). The percentage of HD with antibiotic and M. citrifolia waste did not significantly (P>0.05) differ, but tent to be higher than that of the control. Egg weight with M. citrifolia waste 5 g/kg was significantly (P<0.05) higher than that of control and M. citrifolia waste 15 g/kg. Between antibiotic and M. citrifolia waste did not significantly (P>0.05).differ.  FCR with antibiotic and M. citrifolia waste 5 g/kg was significantly lower than that of control. Between antibiotic and M. citrifolia waste was not significantly different (P<0.05), but FCR with antibiotic and M. citrifolia waste 5 g/kg tent to be lower than that of M. citrifolia waste 10 and 15g/kg. It is concluded that the use of M. citrifolia waste 5 g/kg can substituted antibiotic in layer ration. Key Words: M. Citrifolia Waste, Antibiotic, Egg Production, Layer